2017
DOI: 10.1128/aem.00243-17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gelling Agent and Extracellular Signaling Molecules on the Culturability of Marine Bacteria

Abstract: Only 1% of marine bacteria are currently culturable using standard laboratory procedures, and this is a major obstacle for our understanding of the biology of marine microorganisms and for the discovery of novel microbial natural products. Therefore, the purpose of this study was to investigate if improved cultivation conditions, including the use of an alternative gelling agent and supplementation with signaling molecules, improve the culturability of bacteria from seawater. Replacing agar with gellan gum imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…Molecular surveys have shown that sponges host rich microbial communities (40, 41); however, only a minor component of this richness has been cultivated via the conventional cultivation method (32). Extensive cultivation efforts have made use of several alternative techniques to isolate previously uncultured sponge-associated bacteria, including adding the sponge extracts or its skeleton to the media (42, 43), using oligotrophic media (36), adding antibiotics to inhibit fast-growing bacteria (44), using alternative gelling agent (45), and using in situ diffusion devices (21, 22) and floating filters (42). These alternative approaches yielded an increased novelty of sponge isolates and improved cultivability rates up to 14% in some cases (42).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular surveys have shown that sponges host rich microbial communities (40, 41); however, only a minor component of this richness has been cultivated via the conventional cultivation method (32). Extensive cultivation efforts have made use of several alternative techniques to isolate previously uncultured sponge-associated bacteria, including adding the sponge extracts or its skeleton to the media (42, 43), using oligotrophic media (36), adding antibiotics to inhibit fast-growing bacteria (44), using alternative gelling agent (45), and using in situ diffusion devices (21, 22) and floating filters (42). These alternative approaches yielded an increased novelty of sponge isolates and improved cultivability rates up to 14% in some cases (42).…”
Section: Discussionmentioning
confidence: 99%
“…Media were solidified using 0.75% (w/v) gellan gum (GELRITE, Carl Roth, Karlsruhe, DE), since agar has been shown before to impair the cultivability of environmental bacteria (Narihiro and Kamagata, 2013;Tanaka et al, 2014;Rygaard et al, 2017). Before autoclaving the pH was set to between 8 and 8.5, to achieve a final pH of approximately 8.…”
Section: (A) Platesmentioning
confidence: 99%
“…Only about 1% of marine bacteria can be easily studied using standard laboratory procedures [ 53 ]. This is a major drawback for the understanding of how those microorganisms interact.…”
Section: Examples Of Wto Network Using the Wto R Packagementioning
confidence: 99%